Hubungan Dukungan Keluarga dengan Kepatuhan Minum Obat pada Klien Halusinasi - Karitas, Mirdayata Diana; Fahdi, Faisal Kholid; Yulanda, Nita Arisanti (Universitas Malahayati, 2023)
ABSTRACT Mental health problems are currently experiencing an increasing trend. Long treatment makes some hallucinatory clients have low medication adherence. Analyze the relationship between family support and medication adherence in hallucinatory clients at the Poli Psikiatri Technical Implementation Unit Klinik Utama Sungai Bangkong. This study was a type of quantitative research with correlational design and cross sectional study approach. The number of research respondents was 30 outpatient clients at the Poli Psikiatri Technical Implementation Unit Klinik Utama Sungai Bangkong living with hallucination. The sampling technique used was consecutive sampling. Research instruments were employed to measure family support, namely Perceived Social Support-Family and to measure medication adherence, namely Morisky Medication Adherence Scale-8. The statistical test used in the research was the Spearman Rank correlation test with a p-value of 0.025 (p <0.05). This, indicates that there is a relationship between family support and medication adherence in hallucinatory clients. It can be concluded that, there is a relation between family support and medication adherence in people with hallucinaton at the Poli Psikiatri Technical Implementation Unit Klinik Utama Sungai Bangkong. Keywords: Family Support, Hallucinations, Medication Adherence ABSTRAK Masalah kesehatan jiwa saat ini terus mengalami tren peningkatan. Pengobatan yang panjang membuat beberapa klien halusinasi memiliki kepatuhan minum obat rendah. Penelitian ini bertujuan untuk menganalisis hubungan dukungan keluarga dengan kepatuhan minum obat pada klien halusinasi di Poli Psikiatri UPT. Klinik Utama Sungai Bangkong. Jenis penelitian ini adalah kuantitatif dengan desain korelasional dan pendekatan cross sectional study. Responden penelitian berjumlah 30 orang klien rawat jalan di Poli Psikiatri UPT. Klinik Utama Sungai Bangkong dengan riwayat halusinasi. Teknik pengambilan sampel digunakan consecutive sampling. Instrumen penelitian untuk mengukur dukungan keluarga dengan Perceived Social Support-Family dan mengukur kepatuhan minum obat digunakan Morisky Medication Adherence Scale-8. Uji statistik yang digunakan pada penelitian adalah uji korelasi Spearman Rank dengan nilai p-value 0,025 (p<0,05) yang berarti ada hubungan dukungan keluarga dengan kepatuhan minum obat pada klien halusinasi. Adapun dalam penelitian ini terdapat hubungan dukungan keluarga dengan kepatuhan minum obat pada klien halusinasi di Poli Psikiatri UPT. Klinik Utama Sungai Bangkong. Kata Kunci: Dukungan Keluarga, Halusinasi, Kepatuhan Minum Obat